The last song - Sparks, Nicholas (Sphere, 2009)
Seventeen year old Veronica "Ronnie" Miller's life was turned upside-down when her parents divorced and her father, a former concert pianist and teacher, moved from New York City to Wilmington, North Carolina. Three years later, she remains angry and alienated from her parents, especially her father...until her mother decides it would be in everyone's best interest if she and her younger brother spent the summer in Wilmington with him. Resentful and rebellious, Ronnie rejects all of her father's attempts to reach out to her and threatens to return to New York before the summer's end. But soon Ronnie meets Will, the town's local heartthrob, and the last person she thought she'd ever be attracted to. As Ronnie slowly lets her guard down, she finds herself falling deeply in love, opening herself up to the greatest happiness--and pain--that she has ever known.